Identification of Risk Mitigation Priorities in Lettuce Production (Lactuca sativa L.) at Aswana Hidroponik, Purwokerto - Situmorang, Sawitania Christiany (Agrin, 2024)
The purpose of this research is to: a. Identify risk events that occur in lettuce production activities at Aswana Hydroponics, b. Identify sources of risk events in lettuce production activities at Aswana Hydroponics, and c. Identify risk mitigation priorities as recommendations for improvement and improvement of lettuce production management strategies at Aswana Hydroponics in the future. The analysis in the research was carried out using the first phase of the House of Risk method with a quantitative descriptive approach. The data used in this research is primary data including data: general description of the company, risk events, sources of risk events, impact of sources of risk events, level of loss due to risk events, and the correlation between the two. Based on the results of observations, it is known that there are nine events and sources of risk that occur in the hydroponic lettuce business at Aswana Hydroponics. The two sources of risk that need to be given priority attention are frog eye attack and root rot.Keywords: identification, priority, risk mitigation, lettuce, Aswana Hydroponic.